The Phenomenological Background of Collective Positionality - Emanuele Caminada (Rosenberg & Sellier, 2016)
Searle is convinced that phenomenology is inadequate to face social-ontological problems. Despite his opinion, collective intentionality in its positional effort can be explained through phenomenological reductions. Clarifying how Husserl comes to the evidence of the background within the exercise of the transcendental reduction, it has to be shown how the frame of primordinal reduction could make an inner description of the plural firstperson perspective possible. Finally, some of the reasons that left Husserl to be completely overlooked in the contemporary debate on collective intentionality are exposed. The suspicion that is aroused by Husserl’s transcendental phenomenology could be dispelled if one only considers the social-ontological value of the structure of collective positionality that Husserl claims to be the condition of possibility for the experience of objectivity.